ANALISIS HUBUNGAN PERGERAKAN IHSG TERHADAP HARGA SAHAM PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA TAHUN 2015–2024 - Gustina Natalia Togatorop; Erdiana Br Manik; Tria Indah Syahrani Lubis; Putri Kemala Dewi Lubis (STKIP Subang, 2026)
This study aims to analyze the relationship between the movement of the Jakarta Composite Index (JCI) and the stock prices of LQ45 constituent companies on the Indonesia Stock Exchange during the 2015–2024 period. A quantitative associative approach was employed using panel data regression on 20 firms selected through purposive sampling based on their consistent inclusion in the LQ45 index for at least seven years. The data comprised monthly closing prices of the JCI and individual stock returns, with the BI-7DRR interest rate and IDR/USD exchange rate as control variables, yielding 3,380 panel observations. Analyses included Pearson correlation, Common Effect Model (CEM) estimation, and per-company beta coefficients. Aggregately, no significant relationship was found between JCI returns and LQ45 stock returns (r = 0.029; p = 0.096; F = 0.924; p = 0.428), leading to acceptance of the null hypothesis. However, per-company analysis revealed that banking stocks BBRI, BMRI, BBCA, and BBNI exhibited significant positive correlations (r = 0.267–0.312) with beta coefficients above 1.0 (1.187–1.421), whereas energy stocks such as ADRO and PTBA showed the weakest, non-significant correlations. The interest rate and exchange rate control variables had no direct significant effect. The findings indicate that the JCI–LQ45 relationship is sector-specific; investors may leverage the high-beta characteristics of banking stocks for momentum strategies in bullish phases and the low-beta nature of energy stocks for defensive positioning in bearish markets.